2010
DOI: 10.1302/0301-620x.92b1.22629
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of meniscal repair in the avascular zone using mesenchymal stem cells in a porcine model

Abstract: We hypothesised that meniscal tears treated with mesenchymal stem cells (MSCs) together with a conventional suturing technique would show improved healing compared with those treated by a conventional suturing technique alone. In a controlled laboratory study 28 adult pigs (56 knees) underwent meniscal procedures after the creation of a radial incision to represent a tear. Group 1 (n = 9) had a radial meniscal tear which was left untreated. In group 2 (n = 19) the incision was repaired with sutures and fibrin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 34 publications
0
43
0
2
Order By: Relevance
“…The study on swine model confirmed the beneficial effect of MSC over the ACI [61,62]. Moreover, ovine MSCs have been isolated from bone marrow, expanded, characterized, and injected with transforming growth factor (TGF) b3 in a fibrin clot [63].…”
Section: Pre-clinical Studies In Animal Modelmentioning
confidence: 64%
“…The study on swine model confirmed the beneficial effect of MSC over the ACI [61,62]. Moreover, ovine MSCs have been isolated from bone marrow, expanded, characterized, and injected with transforming growth factor (TGF) b3 in a fibrin clot [63].…”
Section: Pre-clinical Studies In Animal Modelmentioning
confidence: 64%
“…Thus in the rabbit, the vascular region extends only 0.7-1 mm from the meniscosynovial junction, and 1.3 mm from this junction is considered to be in the avascular zone [ 21 ]. In the pig, the vascular pattern is similar to human [ 22 ], and in the dog, the peripheral 25 % of the meniscus is vascular [ 19 ]. Meniscal lesions in the vascularized zone have greater reparative ability than in the avascular zone, where lesions frequently fail to heal.…”
Section: Vascular Supplymentioning
confidence: 92%
“…In pig, radial tears at the junction of the anterior horn and pars intermedia extending from the inner zone for two thirds of the width do not heal but development of PTA was not evaluated [ 22 ].…”
Section: Radial Tearsmentioning
confidence: 99%
“…In another study on pigs, the authors were able to show substantial healing of torn avascular menisal tissue impregnated with mesenchymal stem cells compared to a control model where no healing was observed [35]. However, they noted that the me chanical properties of the healed meniscus were inferior to the normal native tissue.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 94%